Laboratory Substantiation of Thermoelectric Method for Monitoring Contact Resistance; Russian Journal of Nondestructive Testing; Vol. 58, iss. 12 - Abouellail A. A. S. A. R. Ahmed Ali Sabri Ahmed Refaat; Chang Jianglei; Soldatov A. I. Aleksey Ivanovich; Soldatov A. A. Andrey Alekseevich; Kostina M. A. Maria Alekseevna; Bortalevich S. I.; Soldatov D. A. Dmitry Alekseevich (2022, 2022)
Title screen